2016
DOI: 10.1177/1526602816649588
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiation Exposure Associated With Intraoperative Cone-Beam Computed Tomography and Follow-up Multidetector Computed Tomography Angiography for Evaluating Endovascular Aneurysm Repairs

Abstract: ceCBCT offers the chance for immediate intraoperative revisions of endograft-related problems. Requiring only a single-phase acquisition, ceCBCT is associated with a considerable reduction in ED (50%-75%) compared to standard 3-phase MDCT angiography after EVAR. On the other hand, MDCT has a larger field of view and is associated with less radiation exposure for a single phase (reduction of 20%-60%) if only the stented region is covered; however, MDCT angiography also uses larger amounts of contrast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…The results of this study align most closely with those of Stuewe et al, indicating that, when using clinical modes of acquisition, radiation doses from FPCT are 100–200% higher than those from MDCT. Kwok et al found that radiation doses during abdominal imaging using fixed techniques were about 50% higher in FPCT compared to MDCT .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study align most closely with those of Stuewe et al, indicating that, when using clinical modes of acquisition, radiation doses from FPCT are 100–200% higher than those from MDCT. Kwok et al found that radiation doses during abdominal imaging using fixed techniques were about 50% higher in FPCT compared to MDCT .…”
Section: Discussionsupporting
confidence: 90%
“…Previous investigators have used different methods in attempts to answer these questions. Steuwe et al compared FPCT to MDCT for endovascular aneurysm repair (EVAR) and found effective doses ( E ) of 4.9 mSv for FPCT compared to 2.6 mSv for MDCT for single phase imaging with matched imaged length and both scans under automatic exposure control (AEC) . Bai et al measured E of 7.04 mSv for the FPCT compared to 8.42 mSv for MDCT using fixed technique at 120 kV, and reported lower contrast‐to‐noise ratio (CNR) and higher noise for FPCT compared to MDCT .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the impact of CBCT after F-BEVAR. [1][2][3]9,15 They have reported that endoleaks and kinking were detected intraoperatively with a better sensitivity than with 2D completion angiograms, possibly leading to immediate correction and reduction of early reintervention rate. According to Tenorio et al, 9 up to 1 of 5 patients could have positive findings leading to a prompt revision after CBCT, especially after F-BEVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such intraoperative radiation reduction may also have an impact on the OR staff who are subjected to scatter radiation during the procedure and who have been shown to have more malignancies than staff members not performing fluoroscopically-guided procedures. 2 However, even if a CBCT is associated with significant radiation exposure, 10 it does not necessarily affect the staff because they can be outside the room during exposure. On the contrary, the acquisition of the 2 projections in fluoroscopy requires the proximity of the surgeon to the machine in order to adjust the table position.…”
Section: Discussionmentioning
confidence: 99%